Advancing New Product Development Practices for Innovation and Growth in Malaysia’s Automotive Industry - Yusof, Mohamed Suhaimi; Zaini, Ahmad Fauzi Ahmad; Othman, Norreha; Jali, Muhamad Nizam; Manan, Dewi Izzwi Abdul; Seman, Shahri Abu; Abidin, Zila Zainal (Journal of Posthumanism, 2025)
This research aims to look at the factors that are essential in Malaysia automotive industry for effective New Product Development that include IT capability, NPD strategy and NPD process. IT capability enhances innovation and collaboration through state of the art tools such as predictive analysis and Industry 4.0 technologies that mean real time decision making and the ability to respond to change faster. NPD strategy focuses on how organizational goals can be achieved in the light of emerging market needs, criteria such as sustainability, customer feedback and market analysis to determine which projects will have the biggest impact in the long term. As for the processes, at NPD the focus is made on the methodologies, which provide structure to the developmental process, include stage-gate frameworks, and lean activities to enhance the works’ efficiency, avoid waste and deliver the highest quality. Based on a survey of automotive vendors, the analysis based on PLS-SEM identifies combined and bidirectional effects of these factors in creating competitive advantage and sustainable innovation. New technologies such as AI and IoT even increase the possibilities of NPD excellence: disclosuring effective practices for improving product development within the condition of high competitiveness.